Conversations about Philosophy. Volume 2 . - Burton, Howard (Toronto : Open Agenda Publishing, 2021)
Conversations About Philosophy, Volume 2, is a five-part Ideas Roadshow Collection of carefully-edited Ideas Roadshow Conversations featuring leading researchers with a detailed preface highlighting the connections between the different books. All five books include a detailed essay setting up the different ideas and questions for discussion at the end of each chapter. The following experts have participated in this Collection: 1. Brian Epstein, Associate Professor of Philosophy at Tufts University;2. Onora O'Neill, Emeritus Professor of Philosophy at the University of Cambridge and a crossben.
IV. Modern Implications -- V. Philanthropic Post-Humanism -- Continuing the Conversation -- Meaningfulness -- A conversation with Susan Wolf -- Introduction -- I. Philosophical Engagement -- II. Investigating Motivation -- III. Exploring Fulfillment -- IV. Subjective meets Objective -- V. Objectivity Emerges -- VI. Why Meaning Matters, Part I -- VII. Enter Sisyphus -- VIII. Frames of Reference -- IX. Why Meaning Matters, Part II -- X. Towards a Meaningful World -- XI. Beyond Happiness -- Continuing the Conversation
Description based upon print version of record.
JSTOR
Keywords: Kant, Immanuel, -- 1724-1804.; Spinoza, Benedictus de, -- 1632-1677.; Kant, Immanuel, -- 1724-1804; Spinoza, Benedictus de, -- 1632-1677; Philosophy; Meaning (Philosophy); Philosophy; Philosophie; Signification (Philosophie); philosophy; Renaissance; HISTORY; Ancient & Classical; History & Surveys; PHILOSOPHY; Meaning (Philosophy); Philosophy